Students’ learning obstacles in understanding of fraction concept during online learning - Mimi Hariyani; Herawati Herawati; Melly Andriani; Suherman Suherman (Mahesa Research Center, 2023)
This study described students' learning obstacles in understanding fraction concepts at elementary schools during online learning. The subject was 38 person of fifth-grade students of elementary schools in Bandung and Pekanbaru, Indonesia. In this study, data was collecting through tests, interviews, and curriculum documents. The data was analyzed by reducing, presenting, and making conclusions. The results show that students faced three learning obstacles: ontogenic, epistemological, and didactical. The ontogenic obstacle is caused by students' inability to understand that the fraction parts must be the same. The epistemological obstacle is an obstacle caused by the inability of students to understand the equivalence of fractions. The didactical obstacle is caused by the teaching material presented had not introduced the concept of fractions comprehensively, so the students cannot interpret fractions ultimately.